Guinea - The Equity and School Improvement Project - World Bank (Washington, DC, 2012)
An emphasis on primary education, especially in the rural areas, has been demonstrated to be an effective instrument in tackling poverty. The Government of Guinea's National Education for All Program, adopted in 1990, aimed to expand the gross primary school enrollment rate from 28 percent to 53 percent by the year 2000, increase the efficiency of resource use within the sector, increase government support for basic education, and improve the quality of education. The project's objectives are: (a) to increase the gross primary school enrollment rate from 40 percent to 53 percent (during the project period), increase rural student participation from 20 percent to 40 percent, and increase the gross primary school enrollment rate of girls from 29 percent to 42 percent; (b) to improve the quality of education at the primary and lower secondary levels; and (c) to develop capacity within the ministry of pre-university education and vocational training to plan, monitor, and manage the sector and sector outputs in a sustainable manner. The need to address poverty and gender issues significantly informed the design of the project. All project activities were designed to impact favorably on girls schooling. In pursuit of the above broad objectives, specific implementation goals were targeted and are monitored during annual project reviews.